PROPOSALS FOR A LA PAMPA’S LAW OF STATE’S RESPONSABILITY (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
The theory that considers the State’s Liability as part of the public law, and that its regulation constitutionally corresponds to the Provinces has been imposed. In the absence of applicable local regulations, the Superior Court of Justice of La Pampa has determined that the Civil and Commercial Code applies by analogy. The national Congress has passed the law No. 26,944, which regulates the State’s Liability at a federal level and encourage the Provinces to adhere to its provisions and apply them to their own actions. With this scenario, it is necessary andconvenient to establish rules to regulate the State’s Liability and/or adapt the application by analogy of the CCyC to the relevant public law principles.
Keywords: state's liability; provincial public law; lawful acts liability; unlawful acts liability